Positive emotions and employees’ protection-motivated behaviours: a moderated mediation model - Zhen, Jie; Xie, Zongxiao; Dong, Kunxiang (Journal of Business Economics and Management, 2020)
This study explores the relationship between positive emotions and protection-motivated behaviours by focusing on the mediating role of self-efficacy and the moderating role of information security awareness. Based on a sample of 215 full-time employees from various organizations in China, the results of hierarchical regression and moderated path analysis indicate that positive emotions positively influence protection-motivated behaviours, and self-efficacy partially mediates this relationship. In addition, information security awareness has a positive moderating effect on the relationships between positive emotions and self-efficacy and between self-efficacy and protectionmotivated behaviours. Furthermore, the findings show that information security awareness has a positive moderating effect on the mediating effect of self-efficacy between positive emotions and protection-motivated behaviours. The theoretical and practical implications of these results, as well as directions for future research, are discussed.